The Myth of Inventing the Many-Ηeaded Nome - Almazova, Nina (Hyperboreus, 2024)
Among extant sources, only Pindar (Pyth. 12) and, about 9 centuries later, Nonnus of Panopolis (Dionys. 40. 227–233; 24. 36–38) tell the story of the inventing of the many-headed nome (an instrumental aulos piece depicting with musical means the victory of Perseus over the gorgons): it is said to have been created by Athena to imitate the wailing of the gorgons over decapitated Medusa, of which she was an eyewitness. It is argued that Pindar himself was the author of this etiological legend: he proceeded from two already current myths, that of Perseus patronized by Athena and that of Athena inventing aulos playing, and combined them to please his client, Midas the aulos player, who most probably won the Pythian victory performing exactly the many-headed nome. Nonnus borrowed the myth from Pindar. Geographical speciﬁcations, which are diﬀerent in Pindar and Nonnus, do not contradict this conclusion.